Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1162/glep_a_00108
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Paradoxes of Multilevel Governing: Climate Change Policy in the European Union

Abstract: Abstract. The European Union (EU) has sought to lead the world in the adoption of ambitious climate change mitigation targets and policies. In an attempt to characterize and broadly explain the resulting pattern of EU climate governance, scholars have advanced the term "multi-level reinforcement." This helps to account for the paradoxical situation whereby the EU seeks to lead by example but is itself a relatively leaderless system of governance.Drawing on a much fuller empirical account of the evolution of EU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 26 publications
(1 reference statement)
0
66
0
1
Order By: Relevance
“…Other enabling conditions include the presence of pioneering countries, international networks and the specific characteristics of the instrument in question. Tews et al (2003) suggested that the impact of international forums on policy instrument transfer depends on the existence of transnational entrepreneurship and exploitation of first mover strategies; the promotion of instruments by international actors such as the EU can help provide national leaders with an external source of legitimacy (Jordan et al 2012a).…”
Section: Why Are They Selected?mentioning
confidence: 99%
See 1 more Smart Citation
“…Other enabling conditions include the presence of pioneering countries, international networks and the specific characteristics of the instrument in question. Tews et al (2003) suggested that the impact of international forums on policy instrument transfer depends on the existence of transnational entrepreneurship and exploitation of first mover strategies; the promotion of instruments by international actors such as the EU can help provide national leaders with an external source of legitimacy (Jordan et al 2012a).…”
Section: Why Are They Selected?mentioning
confidence: 99%
“…Pedersen (2007, p. 71) placed more emphasis on the subsequent process of legitimation, arguing that the ecotax innovation that occurred in Denmark, Norway and Sweden was less the recognition of the idea of taxation (something that was well established already in other sectors), but rather learning on the part of policymakers about how to frame the instruments as being legitimate and rational. The knowledge itself was less decisive, as prior experience with taxation gave experts ammunition for those attacking the extension of eco-taxation (Jordan et al 2012a). Nye and Owens (2008) found two equally compelling reasons why UK industry was so willing to embrace emissions trading: desire for a more amenable alternative to the UK Climate Change Levy (i.e.…”
Section: Why Are They Selected?mentioning
confidence: 99%
“…Since no steering systems are presented in the macro-regional strategy, it is difficult to analyze exactly how the strategy will complement national policy in the two case countries. In relation to mainstreaming as a principle in the EU, however, previous studies find scant evidence that such policy integration would be a successful principle of vertical policy implementation [69,70].…”
Section: Finlandmentioning
confidence: 99%
“…NREAP opens new opportunities for the Dutch RES performance as it integrates RES development in the EU area. The updates serve as a highly important addition since the nature of the Dutch energy market itself will be changing due to market size expansion and other new socioeconomic implications [8,9]. The Dutch energy agency predicts that if the NREAP policy on accelerating renewable energy usage is carried out, the share of renewable energy will increase from 4% currently to 8% in 2020.…”
Section: Introductionmentioning
confidence: 99%